CRISPR/Cas9 screens identify key host factors that enhance rotavirus reverse genetics efficacy and vaccine production - Yinxing Zhu; Meagan E. Sullender; Danielle E. Campbell; Leran Wang; Sanghyun Lee; Takahiro Kawagishi; Gaopeng Hou; Alen Dizdarevic; Philippe H. Jais; Megan T. Baldridge; Siyuan Ding (npj Vaccines)
Abstract Rotaviruses pose a significant threat to young children. To identify novel pro- and anti-rotavirus host factors, we performed genome-wide CRISPR/Cas9 screens using rhesus rotavirus and African green monkey cells. Genetic deletion of either SERPINB1 or TMEM236, the top two antiviral factors, in MA104 cells increased virus titers in a rotavirus strain independent manner. Using this information, we optimized the existing rotavirus reverse genetics systems by combining SERPINB1 knockout MA104 cells with a C3P3-G3 helper plasmid. We improved the recovery efficiency and rescued several low-titer rotavirus reporter and mutant strains that prove difficult to rescue otherwise. Furthermore, we demonstrate that TMEM236 knockout in Vero cells supported higher yields of two live-attenuated rotavirus vaccine strains than the parental cell line and represents a more robust vaccine-producing cell substrate. Collectively, we developed a third-generation optimized rotavirus reverse genetics system and generated gene-edited Vero cells as a new substrate for improving rotavirus vaccine production.